Mauritius : Financial System Stability Assessment-Update. (IMF Staff Country Reports; Country Report ;, 2008)
The key findings of Mauritius's Financial System Stability Assessment update are discussed. The Mauritian financial system has been resilient to recent economic shocks, and banks have adequate capital buffers against a range of shocks to their credit portfolios and liquidity positions. Infrastructural reforms have improved the business environment but there are several areas, such as insolvency rules, monetary policy, and debt management, where further steps should be given high priority. Advanced risk assessment methods, including stress testing, would be a valuable addition to supervisors' planning tools and capacity.